Health Education among Medical Students: A Challenge Worth Accepting - Nikolaos Plastaras; Angeliki Baimaki; Sotirios Karagiannidis; Aikaterini Giannaki; Nikolaos Vlachopoulos; Emmanouil Smyrnakis (University Library System, University of Pittsburgh, 2022)
World health education should be an integral part of every medical school's curriculum. Unfortunately, this is not always the truth. In an effort to bring medical students of our school closer to Health Education, we developed and implemented a Health Education Program. This Program featured the inclusion of medical students as coordinators, along with the experts of the Team. Herein we share our experience throughout this journey, the obstacles that we faced, and our advice for anyone who might be interested in developing such a program. Furthermore, we discuss what the impact of including medical students as team members and program coordinators can be.